2018
DOI: 10.1002/jgh3.12083
|View full text |Cite
|
Sign up to set email alerts
|

Kombiglyze (metformin and saxagliptin)‐induced hepatotoxicity in a patient with non‐alcoholic fatty liver disease

Abstract: A 33‐year‐old man was referred with hyperosmotic symptoms of 4 weeks. Clinical examination showed palpable hepatomegaly and no stigmata of liver disease. Findings were random glucose 16.6 mmol/L, HbA1c 12.4%, triglyceride 6.2 mmol/L, normal LFTs and ultrasound liver: increased echogenicity. Management consisted of dietician referral and commencement of metformin 500 mg bd, diamicron MR 60 mg od, and fenofibrate 145 mg od. He was non‐compliant, complaining of “heaviness of head” after consuming oral diabetic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…As for saxagliptin, one case of hepatotoxicity has been reported to date. Thalha et al (2018) revealed that Kombiglyze (metformin with saxagliptin) induced cholestasis in a patient with nonalcoholic steatohepatitis [13]. Therefore, further studies are required to confirm the covalent binding of saxagliptin to the cysteine residues of endogenous proteins in animals and humans to precisely predict the potential of DILI from saxagliptin in clinics.…”
Section: Identification Of the Reactive Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…As for saxagliptin, one case of hepatotoxicity has been reported to date. Thalha et al (2018) revealed that Kombiglyze (metformin with saxagliptin) induced cholestasis in a patient with nonalcoholic steatohepatitis [13]. Therefore, further studies are required to confirm the covalent binding of saxagliptin to the cysteine residues of endogenous proteins in animals and humans to precisely predict the potential of DILI from saxagliptin in clinics.…”
Section: Identification Of the Reactive Metabolitesmentioning
confidence: 99%
“…However, saxagliptin-induced liver injury has been reported in rare cases. Thalha et al recently presented a case of hepatotoxicity caused by Kombiglyze (saxagliptin of 5 mg plus metformin of 1000 mg) in Malaysia [ 13 ]. The patient, showing palpable hepatomegaly and no stigmata of liver disease, demonstrated increased alanine aminotransferase (307 IU/L) and gamma-glutamyltransferase (808 IU/L) levels one week after the first Kombiglyze administration.…”
Section: Introductionmentioning
confidence: 99%
“…Some preclinical models may provide insight into a single characteristic of NASH, but none can provide a comprehensive overview of all changes in enzyme and transporter expression or function 15 . A small number of studies have reported drugs that present risk of ADRs in patients with preexisting liver diseases ( Table 1 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , ...…”
Section: Adverse Drug Reactions In Liver Diseasementioning
confidence: 99%
“…A small number of studies have reported drugs that present risk of ADRs in patients with preexisting liver diseases ( Table 1 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ,…”
Section: Adverse Drug Reactions In Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation